Perioperative Nutritional Status of Digestive Surgery Laparotomy Surgery - Iqbal, Aulia; Wijaya, Dadik Wahyu; Lubis, Bastian (CoinReads Media Prima, 2022)
Introduction: Laparotomy is one of the most frequently performed surgical procedures. Surgery causes a stress response that increases the risk of experiencing malnutrition, especially in patients undergoing laparotomy. Malnutrition can increase the risk of adverse outcomes in postoperative patients. This study aims to evaluate perioperative nutritional status in patients who will undergo laparotomy surgery at Haji Adam Malik General Hospital Method:This research is an observational study with a prospective design. This study involved 65 research subjects withthe sampling technique was carried out by non-probability sampling, namely consecutive sampling. Results:The majority of study subjects had BMI ≥18.5, without weight loss >3.6 kg in the last 6 months, without a history of food intake <50% portion in the last 1 week, and albumin value ≥3.0 pre- and post- operative. Postoperatively. The number of subjects with PONS value ≥1 changed from 33.85% before surgery to 52.31% after surgery. There was a significant change in PONS values ​​before and after laparotomy (p = 0.001). Conclusion:Statuspost-operative nutritional study subjects decreased compared to before surgery. A significant increase in PONS scores also occurred after laparotomy.